Sarcasm In The Comments Section of The Instagram Account @pertamina - Rahman, Faiza Fauzia; Markhamah, M (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2025)
This study investigates the use of sarcasm in the comment section of the official Instagram account @Pertamina as a form of public reaction to energy services and policy issues. Using a qualitative descriptive approach with a pragmatic orientation, the study analyzed comments, of which 126 were identified as containing sarcastic expressions. The data were examined using Miles and Huberman's interactive analysis model and classified based on Camp's (2011) framework, which distinguishes propositional, lexical, and illocutionary sarcasm. The findings show that propositional sarcasm dominates (68 instances), followed by lexical (34) and illocutionary sarcasm (24). This distribution indicates that netizens frequently employ sarcasm to express direct and explicit criticism toward Pertamina, a state-owned enterprise responsible for sensitive public services such as fuel pricing and policy transparency. The study's contribution lies in extending Camp's theoretical model to the Indonesian digital context and in highlighting how sarcasm functions as a mechanism of social control and civic engagement. The findings suggest that sarcasm plays a significant role in shaping public discourse and evaluating institutional performance on social media.